Impact analysis of distributed generation on protection devices coordination in power distribution systems - Reiz, Cleberton [UNESP]; Leite, Jonatas Boas [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Integration of distributed generation in power distribution networks provides many advantages and challenges to electric power system. Among challenges are the increase in levels of short-circuit currents and changes of power flow direction. These characteristics can interfere in the interruption capacity of protection devices, which are responsible for maintaining the integrity of distribution networks. Therefore, it is essential to understand the effects of distributed generation on protection systems to determine strategies that aim to solve the challenges imposed by this technology. The present work, first, proposes the mathematical formulation to coordinate overcurrent relays and fuse links, considering permanent and temporary faults. The solution is obtained through a dedicated genetic algorithm. Subsequently, this solution method is analyzed under different levels of penetration of distributed generators, allowing to identify points most susceptible to loss of coordination.
Keywords: Circuit analysis computing; Digital relays; Distributed generation; Fuses; Power distribution faults; Power system protection